Three dimensional palladium nanoflowers with enhanced electrocatalytic activity towards the anodic oxidation of formic acid. Issue 3 (3rd December 2014) - Zhang, Bingqing; Peng, Hongliang; Yang, Lijun; Li, Hualing; Nan, Haoxiong; Liang, Zhenxing; Song, Huiyu; Su, Huaneng; Li, Can; Liao, Shijun
Abstract : Pd nanoflowers (Pd-NF) composed of ultrathin Pd nanosheets show significantly enhanced activity towards the electro-oxidation of formic acid compared to ordinary Pd nanoparticles. Abstract : Three-dimensional palladium nanoflowers (Pd-NF) composed of ultrathin Pd nanosheets were synthesized by a solvothermal approach. The Pd-NF catalyst shows 6.6- and 5.5-fold enhancements in mass activity and surface activity compared to normal palladium nanoparticles (Pd-NP) in the electro-oxidation of formic acid.